Menjajaki Kesadaran Pelanggan Pengguna Aplikasi Kredit Digital dari Aspek Keamanan - I Gede Wisnu Satria Chandra Putra; Halim Agung; Rustono Farady Marta (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
The outbreak of cases of illegal online loans and violations of user data privacy have caused digital credit applications to not be recommended as a top priority to meet people's financial needs. On the other hand, the trend shows that digital credit application users tend to continue to increase over time. Therefore, the author initiated this study which aims to see the effect of public awareness on security (X Variable = Security Awareness) on their interest in using online loan applications (Y Variable = Customer Interest). The research was conducted using statistical testing methods with questionnaire-based data collection. The method used is by testing the validity and reliability, then ends with testing the hypothesis. This study succeeded in collecting data from 128 respondents and after processing and analyzing the data, it was obtained that security awareness had a significant positive effect. The findings of this study indicate that the factor of public awareness of security drives their desire to use digital credit applications.